Analisis Strategi Sistem Informasi Menggunakan Framework Ward & Peppard pada PT Telering Distrindo - Aditya Pratama Putra; Muhamad Albaihaqi Naufal Andewa; Feri Widiyanto; Ito Setiawan; Ardani Eka Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
PT Telering Distrindo is a telecommunications distribution and retail company whose operations rely heavily on information systems. As the business expands and transaction volumes increase, higher demands for system security and reliability require a strategic evaluation of information technology (IT) implementation to ensure alignment with business objectives. This study aims to analyze the condition of the IT infrastructure at PT Telering Distrindo and to formulate development strategies using the Ward & Peppard framework. The research methods include literature review, system observation, IT architecture analysis, and interviews with internal stakeholders. The results show that the company has implemented core systems such as aPOSPlus, aBusinessPlus, and the PPOB TR Reload application, which play an important role in supporting business operations. However, several weaknesses remain in system security, integration, and IT risk management. The SWOT analysis identifies strengths in access control and authentication mechanisms, opportunities to leverage security as a competitive advantage, and threats from cyberattacks and high dependency on IT infrastructure. The study concludes that the Ward & Peppard framework provides a comprehensive strategic perspective and serves as a foundation for developing a more structured, secure, and sustainable IT strategy to support business growth.